Socio-economic circumstances at birth and early motherhood: The case of the "Daughters of the Wall" - Kristin J. Kleinjans (Journal of Economics and Statistics, 2024)
The fall of the Berlin Wall in November 1989 resulted in a severe economic downturn and a stark temporary decline in fertility in East Germany. But did it also affect the fertility of future generations? In this paper, I investigate early motherhood - a marker of lifetime disadvantage - of those born in the years immediately after the fall of the Berlin Wall. Using data from the German Socioeconomic Panel and a difference-in-differences specification comparing the 'Daughters of the Wall' with East Germans born in adjacent years and with West Germans in order to control for region fixed-effects and time-varying confounders, I find that these Daughters of the Wall were more likely to have children in young adulthood if they did not grow up with both of their parents. These results suggest that severe recessions increase early motherhood of those born into disadvantage, increasing the transmission of disadvantage across generations.
Keywords: D91; J13; P30; 330; economic upheaval; fall of the Berlin Wall; fertility; gender inequality; German socioeconomic panel; parental selection; recession